Assessment of Pre- and Post-Operative Quality of Life in Geriatric Patients Undergoing Arthroplasty for Osteoarthritis in a Rural Area: A Pilot Study - Rajan, Redlin Jani; Kartik, Neesha Solanky; Udayakumaran, Narmadha; Bheema, Manisha; Arulmurugan, Ramya; Arumugam, Prathap (Indian Journal of Pharmacy Practice)
Objectives: Osteoarthritis (OA), primarily affecting elderly individuals, leads to joint deterioration and pain. Arthroplasty is a common intervention, but its success should consider overall well-being. This study examines effectiveness in pain relief, mobility improvement, and impact on mental health, social engagement, and quality of life in geriatric OA patients before and after Total Knee Replacement (TKR) using the Oxford Knee Score scale for assessment. Materials and Methods: This prospective observational study included 30 patients with OA who underwent arthroplasty between April to June 2023 and whose quality of life was assessed preoperatively and their postoperative sociodemographic characteristics were assessed using a general information questionnaire. The Oxford Knee Score (OKS) assessed disability before and after TKR, and resting pain was assessed using the visual analog scale. Data analysis was performed using SPSS software with p<0.05 as the significance level. Results: In the age distribution, 38% were 65-70 years old, 45% were men and 55% were women. In terms of family history, 68% reported a history of osteoarthritis in their families. Regarding BMI categories, 48% were overweight. Knee pain has a significant impact on various aspects of participants’ daily lives, including mobility, personal care, work, and recreational activities. The high statistical significance indicates a strong relationship between the reported knee pain and its effects. Conclusion: Arthroplasty significantly enhances quality of life by reducing pain, improving functionality, and enhancing physical capabilities, albeit not to the level of healthy individuals. Recognizing preoperative conditions, lifestyles, and comprehension is pivotal for surgical success. Improved balance is key post-surgery.
Keywords: Osteoarthritis; Arthroplasty; Postoperative Quality of Life; Oxford Knee Score